Pembelajaran pemahaman konsep bilangan bulat pada kelas III Sekolah Dasar dengan menggunakan alat peraga kancing - Rini Purwani Wahyuningsih; Jajang Bayu Kelana (COLLASE (Creative of Learning Students Elementary Education), 2023)
This study aims to determine the scenario and implementation, teacher and student responses, the difficulties of teachers and students in implementing integer learning using button props. The research subjects were teachers and students of class III SD Cerdas Muthahhari, totaling 20 students. The form of this research is descriptive qualitative research. The research procedure includes the stages: preparation, implementation, and evaluation. The research process at the implementation stage includes the implementation of a pre-test to measure the understanding of mathematical concepts before being treated, the treatment stage is to carry out learning using button props, the next stage is an evaluation by carrying out a post-test to see the understanding of mathematical concepts after being treated. The results showed that there was a better understanding of concepts and student activeness in the learning process. This proves that learning integer arithmetic operations using buttons improves students' understanding of mathematical concepts.